PENGARUH JENIS RIMPANG DAN KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT TEMULAWAK (Curcuma xanthorrhiza Roxb.) - Nirwan Sahiri dan Adrianton, Megawati (AGROTEKBIS, 2016)
Temulawak or java ginger is an original plantÂ from Indonesia. It is categorized as one kind of rhizome that mostly used as a raw material of traditional medicine. TheÂ mainÂ components of the substances in temulawak rhizome is âcurcuminâ, protein, starch, and essential oil.Â Atsiri of temulawakÂ oil contains phelandren, kamfer, borneol, xanthorrizol, turmero,Â and sineal. One of the good cultivation techniques to increase the number of plant productions as well as the quality that is using the best quality of seed and appropriate composition of planting media. This researchÂ aimsÂ to obtain the right composition of planting media for every kind of rhizomeÂ onÂ the growth of temulawak seed. The significance of this research is to give informations about the use of a good rhizome type and the right composition of planting media in breeding temulawak. This research usedÂ Factorial Randomized Block DesignÂ model with two factors. The first factor is the kind of different rhizomes which consist of main rhizome and tillers rhizome. The second factor is the composition of planting media consist of: soil, soil and sand (1:1); soil, sand and chicken manure (1:1:1); soil, sand and straw (1:1:1). There are 8 combination of treatments and each treatment is repeated three (3) times. In every experimental unit there are two (2) samples of plant, therefore there are 48 samples of plant. The result of this research showedÂ that the treatment rhizome types, the composition of planting media, and the interaction has an effectÂ on the plantsâ height, number of leaves, girth, and leaf areaÂ at age 4, 6, 8, 10, and 12 weeks after planting. The highest plant height is 74.70 cm, the highest number of leaves is 8.00 leaf, the highest girth is 5.53 cm, and the highest leaf areÂ aÂ is 856,81Â cm2Â by using tillers rhizome and the compositions of soil, sand and chicken manure.